Serological study of vaccinia virus reservoirs in areas with and without official reports of outbreaks in cattle and humans in São Paulo, Brazil - Peres, Marina Gea [UNESP]; Bacchiega, Thais Silva [UNESP]; Appolinário, Camila Michele [UNESP]; Vicente, Acácia Ferreira [UNESP]; Allendorf, Susan Dora [UNESP]; Antunes, João Marcelo Azevedo Paula [UNESP]; Moreira, Sabrina Almeida [UNESP]; Legatti, Emerson [UNESP]; Fonseca, Clóvis Rinaldo [UNESP]; Pituco, Edviges Maristela; Okuda, Liria Hiromi; Pantoja, José Carlos de Figueiredo [UNESP]; et al. (Springer Nature, 2013)
Vaccinia virus (VACV), the etiological agent of an exanthematic disease, has been associated with several bovine outbreaks in Brazil since the end of the global vaccination campaign against smallpox. It was previously believed that the vaccine virus used for the WHO global campaign had adapted to an unknown wild reservoir and was sporadically re-emerging in outbreaks in cattle and milkers. At present, it is known that Brazilian VACV is phylogenetically different from the vaccinia virus vaccinal strain, but its origin remains unknown. This study assessed the seroprevalence of orthopoxviruses in domestic and wild animals and farmers from 47 farms in three cities in the southwest region of the state of São Paulo with or without official reports of outbreaks in cattle or humans. Our data indicate a low seroprevalence of antibodies in wild animals and raise interesting questions about the real potential of wild rodents and marsupials as VACV reservoirs, suggesting other routes through which VACV can be spread. © 2013 The Author(s).